The relations between Principal support and work engagement and burnout: Testing the role of teachers' emotions and educational level - Slišković, Ana; Burić, Irena; Sorić, Izabela (Work (Reading, Mass.), 2019)
One of the resources that may prevent burnout and foster the work engagement of teachers is Principal support. In this study we aimed to further explore the links between Principal support and work engagement and burnout, by testing the role of the teachers' emotions and the educational levels of primary schools. Testing 1) the mediating role of teachers' emotions in explaining the relationship between perceived Principal support and work engagement and burnout, 2) differences in tested constructs, and the structural equivalence of the proposed relationship among constructs, between teachers from two educational levels of primary schools. The study included subsamples of 868 class teachers (lower grades) and 1057 subject teachers (upper grades) employed at 104 primary schools in Croatia. Teachers filled out self-report scales measuring burnout, work engagement, perceived Principal support and the positive and negative emotions experienced in relation to students. Emotions partially mediate the relationship between perceived Principal support and work engagement and burnout among teachers. Although class teachers experience higher levels of positive emotions and work engagement compared to subject teachers, the results confirmed the structural equivalence of the hypothesized model across two education levels of primary school. The Principal support predicts work engagement and burnout in teachers both directly and indirectly via emotions.